2000
DOI: 10.1152/ajpheart.2000.279.4.h1625
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and ATP act by different mechanisms to increase microvascular permeability and endothelial [Ca2+]i

Abstract: Vascular endothelial growth factor (VEGF) increases hydraulic conductivity (L(p)) by stimulating Ca(2+) influx into endothelial cells. To determine whether VEGF-mediated Ca(2+) influx is stimulated by release of Ca(2+) from intracellular stores, we measured the effect of Ca(2+) store depletion on VEGF-mediated increased L(p) and endothelial intracellular Ca(2+) concentration ([Ca(2+)](i)) of frog mesenteric microvessels. Inhibition of Ca(2+) influx by perfusion with NiCl(2) significantly attenuated VEGF-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 32 publications
2
58
1
1
Order By: Relevance
“…VEGF can induce an influx of extracellular calcium into the cell through membrane calcium channels (Criscuolo et al, 1989;Pocock et al, 2000;Garnier-Raveaud et al, 2001). Chelating extracellular calcium, by a 5 s pretreatment with EGTA, abolished the VEGF-induced activation of Figure 2 RAFTK/Pyk2, but not FAK, is required for VEGF stimulation of p38 MAPK.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF can induce an influx of extracellular calcium into the cell through membrane calcium channels (Criscuolo et al, 1989;Pocock et al, 2000;Garnier-Raveaud et al, 2001). Chelating extracellular calcium, by a 5 s pretreatment with EGTA, abolished the VEGF-induced activation of Figure 2 RAFTK/Pyk2, but not FAK, is required for VEGF stimulation of p38 MAPK.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether Ca 2ϩ store release was sufficient to increase L p in the absence of Ca 2ϩ influx, the irreversible SERCA inhibitor 100 nM TG was perfused with the nonspecific cation channel blocker 5 mM NiCl 2 (Ni 2ϩ ). TG (100 nM) has previously been shown in this laboratory to transiently increase L p in the presence of Ca 2ϩ influx (25). Vessels were perfused with 1% BSA in FR and rat erythrocytes for a variable time period until the baseline L p stabilized and then perfused with TG and Ni 2ϩ for 20 min.…”
Section: Statisticsmentioning
confidence: 99%
“…We have assumed that this is due to a delayed increase in [Ca 2ϩ ] i in response to these agonists, because previous work (25), where [Ca 2ϩ ] i and permeability were measured in the same model (although in different vessels), showed that there was a distinct time lag between the application of TG to the cells and the increase in both [Ca 2ϩ ] i and permeability. This is in contrast to many studies of endothelial cells in culture where TG results in an immediate transient increase in intracellular Ca 2ϩ , followed by a sustained increased [Ca 2ϩ ] i (8).…”
Section: Release Of Ca 2ϩ From Intracellular Stores Is Sufficient To mentioning
confidence: 99%
See 1 more Smart Citation
“…A ligação do VEGF a esses receptores causa influxo de cálcio citoplasmático, aumentando sua concentração em até quatro vezes, mudança da forma, divisão e migração celular (17,18,(31)(32)(33). Esse aumento da permeabilidade das vênulas às macromoléculas permite que proteínas plasmáticas extravasem para o espaço extravascular, levando a coagulação do fibrinogênio e deposição de gel de fibrina que serve como matriz provisória para o crescimento de novos vasos sanguíneos (15,17,18,23).…”
Section: Angiogêneseunclassified